2019
DOI: 10.1111/jocn.14747
|View full text |Cite
|
Sign up to set email alerts
|

Tokenism or true partnership: Parental involvement in a child’s acute pain care

Abstract: Aims and objectives To explore parental involvement in the child's acute pain care and establish ways in which parental preferences for involvement in their child's care can be identified, facilitated and enhanced by nurses. Background Despite growing evidence supporting effective acute pain management in children and the availability of national and international practice guidelines, children still experience acute pain. Involving parents in their child's pain care has been identified as being a central tenet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(63 citation statements)
references
References 41 publications
(83 reference statements)
2
61
0
Order By: Relevance
“…Shaw, Suonpera's study of NICU documentation is a good example as it demonstrated that minimal attention was given to parental involvement in nurses' notes. Although the lack of parental involvement as an outcome has strong evidence in the literature, little is known about the process by which parents are advertently or inadvertently excluded from care . The current study sheds light on this process by articulating nurses' experience of negotiating spaces with families and their associated gatekeeping comportments.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Shaw, Suonpera's study of NICU documentation is a good example as it demonstrated that minimal attention was given to parental involvement in nurses' notes. Although the lack of parental involvement as an outcome has strong evidence in the literature, little is known about the process by which parents are advertently or inadvertently excluded from care . The current study sheds light on this process by articulating nurses' experience of negotiating spaces with families and their associated gatekeeping comportments.…”
Section: Discussionmentioning
confidence: 92%
“…Despite parents' desire to be implicated in care, parental involvement has remained parsimonious . Shaw, Suonpera's study of NICU documentation is a good example as it demonstrated that minimal attention was given to parental involvement in nurses' notes.…”
Section: Discussionmentioning
confidence: 99%
“…However, nurses may not take as active a role as they could do in managing children's pain, seeing it as the parents' and child's responsibility to inform them when they are experiencing pain [10]. Sharing information with parents and valuing their knowledge of their child and communicating in an equal partnership can establish parents' expectations of involvement in the management of their child's pain [11][12][13]. However, a lack of communication and information provision and poor negotiation of roles can result in missed opportunities for nurses to work in partnership with parents even when parents attempt to be involved and advocate for their child's pain care [11][12][13].…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Where parents (and children) are given information on pain management, studies have shown that this results in satisfaction with care [9]. However, a lack of communication, information provision, and poor negotiation of roles can result in missed opportunities for nurses to work in partnership with parents [11]. Sometimes, information provision can be inconsistent, resulting in parents having sufficient information about some aspects (e.g., the surgical procedure) but not others (e.g., pain medication) [31].…”
Section: Adopting An Individual Approach To the Child And Family And Empowering Parents To Be Effectively Involvedmentioning
confidence: 99%
“…Making evidence-based strategies for vaccination pain management available to parents is critical as parental concern regarding needle pain has been identified as a significant barrier to children receiving their vaccinations [5]. Parents can be powerful advocates for their child's pain management [7], however scientific evidence on pain management is often inaccessible to parents [3], both physically and in terms of language.…”
mentioning
confidence: 99%